Advertisement call of the closely related species Scinax aromothyella Faivovich 2005 and S. berthae (Barrio 1962), with comments on the complex calls in the S. catharinae group - Pereyra, Martín Oscar (2012)
We compare the advertisement calls of Scinax aromothyella and S. berthae, two closely related Neotropical hylid frogs of the S. catharinae group. We studied several individuals from different localities in Argentina, Brazil, and Uruguay. The call parameters analyzed did not allow the discrimination between the two species. Like in other species of the S. catharinae group, the advertisement calls are complex, consisting of short notes with overlapping pulses; an additional trilled note is frequently present, interspersed between the short ones. This complex call structure is common in the S. catharinae group, and was exceptionally reported in other taxa of the S. perpusillus group and the S. ruber clade. The advertisement call in this group is a candidate target for future studies addressing social and environmental factors affecting call structure.